All-atom simulations of bent liquid crystal dimers: the twist-bend nematic phase and insights into conformational chirality. Issue 15 (4th April 2022) - Yu, Gary; Wilson, Mark Richard
Abstract : Atomistic simulations of the liquid crystal dimer, CB7CB, identify the twist-bend nematic phase, show phase transitions to the nematic and isotropic phases, and probe the molecular structure and conformational chirality of molecules in these phases. Abstract : The liquid crystal dimer 1, 7-bis-4-(4′-cyanobiphenyl)heptane (CB7CB) is known to exhibit a nematic–nematic phase transition, with the lower temperature phase identified as the twist-bend nematic (NTB ) phase. Despite the achiral nature of the mesogen, the NTB phase demonstrates emergent chirality through the spontaneous formation of a helical structure. We present extensive molecular dynamics simulations of CB7CB using an all-atom force field. The NTB phase is observed in this model and, upon heating, shows phase transitions into the nematic (N) and isotropic phases. The simulated NTB phase returns a pitch of 8.35 nm and a conical tilt angle of 29°. Analysis of the bend angle between the mesogenic units reveals an average angle of 127°, which is invariant to the simulated phase. We have calculated distributions of the chirality order parameter, χ, for the ensemble of conformers in the NTB and N phases. These distributions elucidate that CB7CB is statistically achiral but can adopt chiral conformers with no preference for a specific handedness. Furthermore, there is no change in the extent of conformational chirality between the NTB and N phases. Using single-molecule stochastic dynamics simulations in the gas phase, we study the dimer series CB n CB (where n = 6, 7, 8 or 9) and CBX(CH2 )5 YCB (where X/Y = CH2, O or S) in terms of the bend angle and conformational chirality. We confirm that the bent molecular shape determines the ability of a dimer to exhibit the NTB phase rather than its potential to assume chiral conformers; as | χ |max increases with the spacer length, but the even-membered dimers have a linear shape in contrast to the bent nature of dimers with spacers of odd parity. For CBX(CH2 )5 YCB, it is found that | χ |max increases as the bend angle of the dimer decreases, while the flexibility of the dimers remains unchanged through the series.